Nonlocal Neumann problem for a degenerate parabolic equation - Pukalskyi, I. D. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
In the spaces of classical functions with power weight, we prove the existence and uniqueness of a solution of the nonlocal Neumann problem for nonuniformly parabolic equations without restrictions on the power order of coefficient degeneration. We find an estimate of the solution of this problem in the spaces considered.